CALCULATION MANAGEMENT OF PALM KERNEL LOSSES ON FIBER CYCLONE AT PT. HUTA BAYU MARSADA - Mahrani Arfah; Wirda Novarika; Suliawati Suliawati (Jurnal Ekonomi, 2023)
This research was conducted at PT. Huta Bayu Marsada especially on fiber cyclone units. To produce palm kernel products with good quality, the processing process is carried out as efficiently as possible, one of which is by preventing core losses. The problem in this study is to find out the total percentage of losses and the amount of palm kernel losses to the incoming feed on Fiber Cyclone at PT. Huta Bayu Marsada. Sampling was carried out for 6 (six) days from the fiber cyclone unit and analysis was carried out in the laboratory for 4 (four) components, namely fiber, intact core, broken core, and core + shell. Samples were taken as much as + 1000 grams at 13.00 WIB - 15.00 WIB. The sample is cyclone fiber waste and analysis of core losses from cyclone fiber is carried out in the factory laboratory. The results of the study showed losses of palm kernel on fiber cyclone at PT. Huta bayu marsada for 6 consecutive days is 0.835%; 0.823 %; 0.785 %; 0.732 %; 0.862% and 0.894% which are still in accordance with the standards at this factory, namely ≤ 1.02%. The difference in the results of the sample components is due to the different sample sizes. Factors affecting palm kernel losses in the Fiber Cyclone process are caused by fruit maturity, harvest phase and air velocity on the specific gravity of the sample. The largest number of palm kernel losses occurred on the sixth day of 518.4668 kg, this was influenced by the total % LossesThe largest number of palm kernel losses occurred on the sixth day of 518.4668 kg, this was influenced by the total % Losses. The amount of palm kernel loss to incoming feed is getting bigger because of its thin and flat shape which makes it easy to lift up and causes losses to increase.